Competitividad del sector frutícola: el caso de Apatzingán, México y Changsha, China (1978-2005): una propuesta para su desarrollo regional - Infante Jiménez, Zoe Tamar (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The present investigation is comparatively related with the competitiveness regional frutícola among the region of Apatzingán, Mexico and Changsha, China. Both regions are linked to a productive agricultural system in relation to their territorial specificity. When one speaks of regional competitiveness in the endogenous development we refer to the characterization of a production system that allows the local managers to use their productive factors efficiently, to generate scale economies and to increase the productivity at levels that they allow to improve the competitiveness in the markets. And at the same time, the agricultural appropriate politicians favor the local initiatives, creating a local favorable environment to the production and impulse to the regional development. Nowadays China is one of the countries that mostly not only highlight in the international environment as one of the most competitive economies in the agricultural sector, but in the manufacturer and of services, because it has reached for more than twenty years superior rates of growth to the one 9.2 percent averages yearly.

La presente investigación está relacionada con la competitividad regional frutícola comparativamente entre la región de Apatzingán, México y Changsha, China. Ambas regiones se vinculan a un sistema productivo agrícola en relación a su especificidad territorial. Cuando se habla de competitividad regional en el desarrollo endógeno nos referimos a la caracterización de un sistema de producción que les permite a los empresarios locales utilizar eficientemente sus factores productivos, generar economías de escala y aumentar la productividad a niveles que permiten mejorar la competitividad en los mercados. Y al mismo tiempo, las políticas agrícolas adecuadas favorecen las iniciativas locales, creando un entorno local favorable a la producción e impulso al desarrollo regional. Hoy en día China es uno de los países que mayormente destacan en el ámbito internacional como una de las economías más competitivas no sólo en el sector agrícola, sino en el manufacturero y de servicios, pues ha alcanzado por más de veinte años tasas de crecimiento superiores al 9.2 por ciento promedio anual.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/341; info:eu-repo/classification/cti/5; ININEE-D-2009-0004; Competitividad regional; Sector agrícola; Políticas agrícolas; México-China; Lógica económica